Dietary supplementation with N-acetylcysteine confers a protective effect on muscle and liver in lipopolysaccharide-challenged piglets - Li, Peng; Zhou, Hancong; Yang, Yuzhu; Wu, Mengjun; Zhao, Di; Wang, Lei; Yi, Dan; Hou, Yongqing (Frontiers in Nutrition, 2024)
N-acetylcysteine (NAC) is a well-established antioxidant that offers exciting opportunities for intestinal health in weaned piglets, while the effects of NAC on muscle and liver has not been fully characterized. Therefore, the present study was performed to investigate the effects of dietary supplementation with NAC on muscle and liver in weaned piglets challenged with lipopolysaccharide (LPS). Twenty-four piglets (24-day-old) were randomly assigned to 3 treatment groups, the piglets in the control (CTR) and LPS- challenged (LPS) groups were fed the basal diet and those in the LPS+ NAC group was fed the basal diet supplemented with 500 mg/kg NAC. The animal trial lasted for 21 days. At the end of the trial, piglets in the LPS and LPS+ NAC groups were injected intraperitoneally with LPS (100 μg/kg body weight) and piglets in the CTR group were administrated with an equal volume of normal saline. 3 h later, the blood was collected and tissue samples were obtained after 6 h of LPS or normal saline treatment. The results showed that the level of IL-1β, and the mRNA levels of C-X-C motif chemokine receptor 3 (CXCR3) and interferon- γ (IFN- γ) in the liver were up-regulated, and the mRNA levels of insulin-like growth factor 1 (IGF-1), total glutathione (T-GSH), and the ratio of total protein to DNA in the liver were decreased under LPS challenge (P< 0.05). At the same time, LPS increased the level of H2O2 and decreased the content of T-GSH and DNA in the longissimus dorsi and gastrocnemius muscles (P< 0.05). In addition, the percentage of monocytes and the level of epidermal growth factor (EGF) were down-regulated in the LPS treatment (P< 0.05). Interestingly, dietary NAC supplementation reversed the above changes induced by LPS (P< 0.05). Furthermore, NAC might alleviate the muscle and liver injury in LPS-challenged piglets by regulating the expression of genes related to the type I interferon signaling pathway, as well as hypoxia inducible factor 1 (HIF1) and nuclear factor erythroid-2 related factor 2 (Nrf-2). Our findings suggested that dietary supplementation with NAC could benefit the health of muscle and liver in LPS-challenged weaned piglets.